Thermal aging effect on the tensile and fatigue properties of the narrow-gap TIG welded joints in offshore floating nuclear power plants. (September 2019) - Yu, Weiwei; Fan, Minyu; Jia, Wenqing; Xue, Fei; Yu, Min; Liu, Hui; Chen, Xu
Highlights: An accelerated thermal aging experiment was performed on narrow-gap TIG welded joints at 400 °C up to 30, 000 h. The tensile strength and fatigue life increased with the increasing thermal aging time. More cracks initiated and propagated in ferrite phases and phase boundaries owing to thermal aging embrittlement. A modified life prediction model was proposed for different aging conditions. Abstract: In offshore floating nuclear power plants, the narrow-gap tungsten-inert gas (TIG) welding method is commonly applied to connect various geometries of pipes due to its high efficiency welding under the low heat input of the welding process. However, the narrow-gap TIG welds have a duplex structure and are sensitive to thermal aging mechanism. In this paper, the narrow-gap TIG joints were subjected to a series of accelerated thermal aging tests at 400 °C for 0, 2000, 5000, 13, 000 and 30, 000 h, respectively, to investigate the tensile and fatigue properties at different locations. The test results indicated that the yield strength and the ultimate tensile strength of the narrow-gap TIG welded joints increased with the increasing thermal aging time. Fatigue life increased along with the thermal aging duration. A modified life prediction model was proposed.